Effect of adding alendronate to hormone replacement therapy on bone mineral density in established postmenopausal osteoporosis - (:unkn) unknown (My University, 2000)
Objective: The purpose of this prospective randomized study was to evaluate the impact of adding alendronate to hormone replacement therapy (HRT) in established postmenopausal osteoporosis. Patients: Forty patients were randomly assigned to receive either 0,625 mg. conjugated estrogen with 2,5 mg. medroxyprogesterone acetate (HRT) alone or HRT combined with 10 mg. alendronate daily for one year. Both groups received, a daily supplement of 500 mg. of elemental calcium. Bone mineral density of lumbar spine and femur neck were measured prior to treatment and at the end of one year by dual energy X-ray absorptiometry. Results: Nineteen patients from alendronate and HRT group, 18 patients from HRT group completed the study. HRT group had an increase in bone mineral density of 7,5±0,02% at lumbar spine (p<0.01) and 11,6±0,04% at femur neck (p<0,001). Whereas alendronate and HRT group had a mean increase in bone mineral density of 7,8±0,02% at lumbar spine (p<0.01) and 17,8±0,02% at femur neck (p<0.01). Both treatments were well tolerated. Conclusions: Both HRT alone and HRT combined with alendronate treatments in postmenopausal osteoporosis appears to increase bone mineral density at spine and femur neck. There is a greater increase in bone mineral density at femur with HRT alendronate combination treatment which did not achieve significance.
Keywords: Alendronate; Bone density; Hormone replacement therapy